Poststroke arm and hand paresis: should we target the cervical spinal cord?. Issue 8 (August 2022) - Pirondini, Elvira; Carranza, Erick; Balaguer, Josep-Maria; Sorensen, Erynn; Weber, Douglas J.; Krakauer, John W.; Capogrosso, Marco
Abstract : Despite advances in understanding of corticospinal motor control and stroke pathophysiology, current rehabilitation therapies for poststroke upper limb paresis have limited efficacy at the level of impairment. To address this problem, we make the conceptual case for a new treatment approach. We first summarize current understanding of motor control deficits in the arm and hand after stroke and their shared physiological mechanisms with spinal cord injury (SCI). We then review studies of spinal cord stimulation (SCS) for recovery of locomotion after SCI, which provide convincing evidence for enhancement of residual corticospinal function. By extrapolation, we argue for using cervical SCS to restore upper limb motor control after stroke. Highlights: Permanent motor deficits after stroke, such as loss of dexterity, loss of strength, and aberrant muscle synergies, are the result of damage to the corticospinal tract (CST). In patients with spinal cord injury, electrical stimulation of the lumbosacral spinal cord has an assistive effect (i.e., it enables voluntary control over previously paralyzed limbs). These assistive effects appear immediately upon turning on the stimulation and disappear as soon as it is turned off. Recent data show that spinal cord stimulation (SCS) combined with extensive training can also have a therapeutic effect (i.e., recovery of voluntary motor control in the absence of stimulation). Data from animals and humans show that SCS increases the efficacy of the residual CST. Thus, SCS combined with intense training focused on impairment may be an effective restorative approach for the poststroke arm and hand.